2016
DOI: 10.3920/bm2016.0003
|View full text |Cite
|
Sign up to set email alerts
|

Citrus juice fermented with Lactobacillus plantarum YIT 0132 alleviates symptoms of perennial allergic rhinitis in a double-blind, placebo-controlled trial

Abstract: This study aimed to examine whether citrus juice fermented with Lactobacillus plantarum YIT 0132 (LP0132), which was pasteurised after fermentation, could alleviate the symptoms of perennial allergic rhinitis in a double-blind, placebo-controlled, parallel-group trial. Subjects with perennial allergic rhinitis consumed LP0132-fermented juice (n=17) or unfermented citrus juice (placebo; n=16) once a day for 8 weeks. During the pre-intervention and intervention periods, the subjects recorded nasal symptoms (numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In addition, this fermented beverage exhibited an outstanding performance in terms of anti-fatigue in a mouse weight swimming experiment [92]. According to Harima-Mizusawa et al [93], citrus beverage fermented with L. plantarum YIT0132 had a good effect in relieving the perennial allergic rhinitis symptoms in a double-blind, placebo-controlled trial. Other fermented beverages, such as those of tomato, feijoa, blueberry-blackberry, cactus pear, and prickly pear fruits exhibit a great in vitro anti-inflammatory capacity and help maintain the integrity of intestinal barrier [85,86,94].…”
Section: Fermented Fruit and Vegetable Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this fermented beverage exhibited an outstanding performance in terms of anti-fatigue in a mouse weight swimming experiment [92]. According to Harima-Mizusawa et al [93], citrus beverage fermented with L. plantarum YIT0132 had a good effect in relieving the perennial allergic rhinitis symptoms in a double-blind, placebo-controlled trial. Other fermented beverages, such as those of tomato, feijoa, blueberry-blackberry, cactus pear, and prickly pear fruits exhibit a great in vitro anti-inflammatory capacity and help maintain the integrity of intestinal barrier [85,86,94].…”
Section: Fermented Fruit and Vegetable Beveragesmentioning
confidence: 99%
“…Decomposition of some risky organic compounds present in the fresh juice like: 2-propenenitrile, 2-(acetyloxy); furfuryl alcohol; acetaldehyde; 2,2-diethyl-3-methyloxazolidine, 4h-Pyran-4-one, 3,5-dihydroxy-2-methyl and furan Panda et al [89] Pumpkin L. mali K8 α-glucosidase inhibitory activity with anti-hyperglycemic effect Koh et al [90] Infusion of oak leaves Kombucha culture Anti-hyperglycemic effect and antioxidant activity Gamboa-Gómez et al [91] Blueberry pomace L. rhamnosus GG. L. plantarum-1 and L. plantarum-2 Hypocholesterolemic and anti-fatigue effect Yan et al [92] Citrus L. plantarum YIT0132 Good effect in relieving perennial allergic rhinitis symptoms Harima-Mizusawa et al [93] Tomato, feijoa, blueberry-blackberry, cactus pear, and prickly pear fruits Different LAB strains Great in vitro anti-inflammatory capacity and help to maintain the integrity of intestinal barrier Di Cagno et al [86], Valero-Cases et al [94], Filannino et al [85] Blueberry pomace L. casei CICC20280 Increase of SCFA production and an improvement of fecal microbiota Cheng et al [96] Changbai Mountain vegetables and fruits Naturalized species of bacteria Reduction of Firmicutes/Bacteroidetes ratio, increase of Bacteroidales S24-7 group, Bacteroidaceae, genus Bacteroides and Prevotellaceae in a mouse model study Wang et al [97]…”
Section: Fermented Fruit and Vegetable Beveragesmentioning
confidence: 99%
“…Moreover, fermented orange beverage could reduce cardiovascular risk in mice (Escudero-López et al, 2015), while fermented beetroot juice could modulate the gut epithelium microbiota beneficially and reduce βglucuronidase activity in rats (Klewicka, Zduńczyk, Juśkiewicz, & Klewicki, 2015). In human, consuming pomegranate juice for 3 weeks could significantly enhance plasma and urinary anti-oxidative activities (Gouda, Moustafa, Hussein, & Hamza, 2015), and daily intake of fermented citrus juice could alleviate perennial allergic rhinitis (Harima-Mizusawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fermented milk was prepared as in a previous report [ 15 ] and contained more than 4.0 × 10 10 CFU of L. casei strain Shirota in an 80-ml bottle (LcS-fermented milk). Fermented Satsuma mandarin juice was prepared based on a previous report [ 11 ] and contained more than 6.0 × 10 10 cells of heat-killed LP0132, as measured by the DAPI counting method, in a 125-ml bottle (LP0132-fermented juice). LcS-fermented milk was stored in a refrigerator, whereas LP0132-fermented juice was stored at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Lactobacillus plantarum YIT 0132 (LP0132) potentially induces a high level of IL-10 secretion in vitro , and previous clinical trials showed that LP0132-fermented citrus juice containing heat-killed LP0132 attenuated JCPsis and other allergic symptoms [ 9 , 10 , 11 , 12 ]. In contrast, Lactobacillus casei Shirota (LcS) has high IL-12 productivity in macrophages [ 13 ], and daily intake of fermented milk containing LcS delays the onset of JCPsis symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%